These called left intellectuals: the IPM of PCB and the communist phenomenon in cultural production in post-coup - Czajka, Rodrigo [UNESP] (Univ Estadual Londrina, 2015)
Among the many investigative actions taken by the military with the intention of collecting information about the communist subversion in the post-coup in 1964, one of the forms that really stood out was the Police-Military Investigation (IPM). This research instrument was designed to collect proof and evidence which subsequently formed the basis for criminal proceedings based on the National Security Law (LSN). Among the IPMs that gained greater impact was the Brazilian Communist Party (PCB), mainly because it was the starting point for other surveys that have unfolded in specific investigations. One of them, which is discussed in this article concerns the organization of a left intellectuality that if before the coup ground a debate on the political and social thought in Brazil, after the coup will gain even greater projection for his performance in resistance to the regime military. In the IPM of PCB the intellectual left or communist intellectual are defined by the military reports as having elements of a sophisticated speech of Soviet propaganda, then, should be thoroughly investigated by intelligence services.
Keywords: Military dictatorship; Military investigations; Communism; Intellectuals